Nanostructures: Hindering the Oxidation of Silicene with Non‐Reactive Encapsulation (Adv. Funct. Mater. 35/2013). (17th September 2013) - Molle, Alessandro; Grazianetti, Carlo; Chiappe, Daniele; Cinquanta, Eugenio; Cianci, Elena; Tallarida, Grazia; Fanciulli, Marco
<x xml:space="preserve">Abstract</x> A. Molle and co‐workers engineer a 'silicene sandwich': the encapsulation of silicene layers epitaxially grown on Ag(111) is necessary to avoid oxidation. Al2O3‐based encapsulation of these layers, demonstrated on page 4340, results in a sandwiched structure that can be exploited for the ex situ characterization of silicene, or for devices incorporating a gated silicene sheet. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>